NIFTy galaxy cluster simulations – V. Investigation of the cluster infall region. Issue 2 (23rd September 2016) - Arthur, Jake; Pearce, Frazer R.; Gray, Meghan E.; Elahi, Pascal J.; Knebe, Alexander; Beck, Alexander M.; Cui, Weiguang; Cunnama, Daniel; Davé, Romeel; February, Sean; Huang, Shuiyao; Katz, Neal; et al.
Abstract: We examine the properties of the galaxies and dark matter haloes residing in the cluster infall region surrounding the simulated Λ cold dark matter galaxy cluster studied by Elahi et al. at z = 0. The 1.1 × 10 15 h −1 M⊙ galaxy cluster has been simulated with eight different hydrodynamical codes containing a variety of hydrodynamic solvers and sub-grid schemes. All models completed a dark-matter-only, non-radiative and full-physics run from the same initial conditions. The simulations contain dark matter and gas with mass resolution m DM = 9.01 × 10 8 h −1 M⊙ and m gas = 1.9 × 10 8 h −1 M⊙, respectively. We find that the synthetic cluster is surrounded by clear filamentary structures that contain ∼60 per cent of haloes in the infall region with mass ∼10 12.5 –10 14 h −1 M⊙, including 2–3 group-sized haloes (>10 13 h −1 M⊙ ). However, we find that only ∼10 per cent of objects in the infall region are sub-haloes residing in haloes, which may suggest that there is not much ongoing pre-processing occurring in the infall region at z = 0. By examining the baryonic content contained within the haloes, we also show that the code-to-code scatter in stellar fraction across all halo masses is typically ∼2 orders of magnitude between the two most extreme cases, and this is predominantly due to the differences in sub-grid schemes and calibration procedures that each model uses. Models that do not include active galactic nucleus feedback typically produce too high stellar fractions compared to observations by at least ∼1 order of magnitude.